THE PRINCIPLE OF BALANCE IN THE PROTECTION OF WORKERS AND EMPLOYERS BASED ON LABOR LAW REFORM - Rahmat GM Manik (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
Industrial relations regulation is a fundamental aspect of the national employment system, aiming to bridge the interests of employers and workers fairly and reflect the principle of balance. This study aims to determine the principle of equitable balance between worker protection and business flexibility in the reform of national labor law. This research uses a normative juridical approach focused on a literature review and analysis of relevant legal principles, concepts, and theories. Previous regulations emphasized worker protection as an effort to prevent injustice to vulnerable workers. The reform of labor law through the Job Creation Law seeks to reposition the balance by providing greater flexibility for employers and reducing the burden of labor costs, for example through adjustments to severance pay and expansion of PKWT (Working Permit) contracts. The main finding is that the reform brings a shift in the value of normative balance, focusing more on economic efficiency and business certainty for employers, while still striving to maintain worker fairness through schemes such as the Job Loss Guarantee. This reform, while providing operational convenience for employers, raises crucial questions about whether an optimal and equitable balance has been achieved, or whether it has instead created a new imbalance in which basic worker rights are sacrificed for economic flexibility. A just balance demands recognition of the strengths and vulnerabilities of both parties, as well as the formulation of regulations that enable inclusive economic growth and adequate social protection.